2011
DOI: 10.1292/jvms.10-0492
|View full text |Cite
|
Sign up to set email alerts
|

Extended Exposure to Trichostatin A after Activation Alters the Expression of Genes Important for Early Development in Nuclear Transfer Murine Embryos

Abstract: ABSTRACT. The low viability of embryos reconstructed by somatic cell nuclear transfer (SCNT) is believed to be associated with epigenetic modification errors, and reduction of those errors may improve the viability of SCNT embryos. The present study shows the effect of trichostatin A (TSA), a strong inhibitor of histone deacetylase, on the development of murine SCNT embryos. After enucleation and nuclear injection, reconstructed murine oocytes were activated with or without TSA for 6 hr (TSA-6 hr). After activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…It is generally believed that compared with the IVF embryos, the expression pattern of pluripotent-related genes in SCNT embryos tend to be lower, so these genes are thought as critical indicators of the blastocyst quality (Inoue et al, 2002; Aston et al, 2010; Kang & Roh, 2011). Thus, in this study, to determine if overexpression KDM4D could affect the blastocyst quality of buffalo SCNT embryos, the expression level of pluripotency-related genes were detected through RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that compared with the IVF embryos, the expression pattern of pluripotent-related genes in SCNT embryos tend to be lower, so these genes are thought as critical indicators of the blastocyst quality (Inoue et al, 2002; Aston et al, 2010; Kang & Roh, 2011). Thus, in this study, to determine if overexpression KDM4D could affect the blastocyst quality of buffalo SCNT embryos, the expression level of pluripotency-related genes were detected through RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference in Nanog expression between the long-term and short-term groups cannot be exactly explained, short-term treatment with TSA might not be the optimal exposure duration of TSA for effective modification of Nanog gene. In ridents, extended exposure to TSA after activation altered the expression of genes related to pluripotency (OCT4, NANOG) and early embryonic development (FGF4, CDX2) in cloned embryos [17]. In addition, it was reported that nuclear reorganization of centromeric/pericentromeric sequences is often abnormal in SCNT embryos and is improved by TSA treatment [2525].…”
Section: Discussionmentioning
confidence: 99%
“…Compatibility of mitochondrial DNA haplotypes between donor cells and host oocytes improves reprogramming efficiency possibly by epigenetic modification. To increase the SCNT viability, treatment with chemicals that causes chromatin modification like Trichostatin-A (TSA) decreases expression of histone deacetylase (HDAC1 and HDAC2) and DNA methylation (DNMT3a and DNMT3b) while increases the expression of histone acetylation (P300 and CBP), pluripotency (OCT4 and NANOG) genes [55]. Histone deacetylase inhibitor valproic acid (VPA) enabled reprogramming of human fibroblasts with only Oct4 and SOX2 [56].…”
Section: The Reprogramming Vectorsmentioning
confidence: 99%
“…TSA-treated embryo showed decreased expression of histone deacetylase (both HDAC1 and HDAC2) and DNA methylation genes (DNMT3a and DNMT3b) where expression levels increased for expression of histone acetyltransferase (P300 and CBP) and pluripotency markers (OCT4 and NANOG). Thus chemicals like TSA can be used to compensate for the shortcomings of iPS [55]. Epigenetic changes happen when differentiation takes place from pluripotency and vice versa [69].…”
Section: The Epigenetical Modificationmentioning
confidence: 99%